1966
DOI: 10.1128/jb.92.5.1555-1561.1966
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Infectivity and Physical Virus Particles in Human Cytomegalovirus

Abstract: Infectivity titers [measured as plaque-forming units (PFU)] and particle counts by the sedimentation pseudoreplication technique were determined for crude, unpurified, intracellular preparations of two different strains of human cytomegalovirus. Unlike the high particleinfectivity ratio of 106 to 108 previously reported for these viruses, the number of total particles per PFU ranged from 160 to 490 with strain AD-169 and from 176 to 1,050 for strain C-87. Interpretation of particle-PFU ratios of intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 17 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In this line, we cannot rule out that the lack of staining of some viral particles with anti‐HCMV gH antibodies may be due to inaccessibility by antibodies or gold particles, or that some virions fail to incorporate HCMV gH and the normal complement of viral envelope glycoproteins into their membrane, resulting in non‐infectious viral particles. In support of this notion, it has been shown that the ratio of viral particles to infectious virus is unusually high for HCMV (Benyesh‐Melnick et al. , 1966).…”
Section: Discussionmentioning
confidence: 89%
“…In this line, we cannot rule out that the lack of staining of some viral particles with anti‐HCMV gH antibodies may be due to inaccessibility by antibodies or gold particles, or that some virions fail to incorporate HCMV gH and the normal complement of viral envelope glycoproteins into their membrane, resulting in non‐infectious viral particles. In support of this notion, it has been shown that the ratio of viral particles to infectious virus is unusually high for HCMV (Benyesh‐Melnick et al. , 1966).…”
Section: Discussionmentioning
confidence: 89%
“…We are investigating preliminary evidence which suggests that the CMV antigen sensitizing the sheep erythrocyte is a soluble antigen, whereas the antigen reacting in the CF test is a combination of both viral and soluble components (1). Different sera should contain different proportions of antibody to the viral and soluble antigens.…”
Section: Discussionmentioning
confidence: 99%
“…All four viruses were kept in passage in HEL fibroblasts as described elsewhere (4,11). Cellfree virus stocks were prepared as described previously (1,4,11) and kept at -90 C in the presence of 35% sorbitol (11). Virus infectivity was determined by the modified microplaque technique (11).…”
Section: Methodsmentioning
confidence: 99%